Ideological and artistic features screenplay by L. Ulitskaya "The Plague, or CDC in the City" (1978-2020) - Khalil, Hadeel Ismaeel (Al-Adab Journal, 2022)
The article analyzes the ideological and genre features of L. Ulitskaya's work "The Plague, or OOI in the City", examines the features of building an artistic whole, ways of creating images of characters and their characteristics, stylistic features of the work.